Comparison of fatigue characteristics for some selected structural materials under bending and torsion - Kurek, М.; Łagoda, Т. (Фізико-хімічна механіка матеріалів, 2011)
The paper presents a review of the multiaxial fatigue criteria including a ratio of normal and shear stresses. The paper also contains fatigue characteristics for bending and torsion of some selected constructional materials. The ratio of normal stresses to shear stresses was determined for the defined number of cycles Nf in the range 5⋅10⁴÷2⋅10⁶. Moreover, from the performed analysis of fatigue equations and the relative difference R it appears that materials can be divided into groups for which it is possible or it is not possible to apply the constant value of the considered ratio in the criteria including this ratio.